ANALISIS PENGARUH CITRA TOKO DAN HARGA KOMPETITIF TERHADAP KEPUTUSAN PEMBELIAN PADA TOKO H.A LAURY DI SEMARANG - Putri, Adriana Lantika; Ferdinand, Augusty Tae (Faculty of Economics and Business Diponegoro University, 2016)
Intense competition in the clothing store business has made H.A Laury Semarang revenues decreased. This study aims to explain the influence of the service quality, product quality, and competitive pricing, in order to influence purchasing decision which store image is used as an intervening variable between service quality and product quality. This study was conducted at H.A Laury Semarang. This study was conducted by taking samples using non probability sampling technique by purposive sampling method, the respondents are consumer who have bought in H.A Laury Semarang. Used as a sample of 100 respondents to fill out a questionnaire which consist of open and closed quetions. The result show that service quality and product quality has positive and significant impact on store image, and store image has a positive and significant effect to purchasing decision. Competitive pricing also has a positive and significant effect to purchasing decision.